The effect of smoking in inflammatory bowel disease outcomes - Alzahrani, Basil A.; Aljuhani, Jamal A.; Badri, Ziyad A.; Alshamrani, Rayan M.; Algaows, Faisal Suliman; Ahmed, Mohamed Eldigire (Frontiers in Gastroenterology, 2024)
BackgroundThe hallmark of inflammatory bowel disease (IBD) is a persistent inflammation of the digestive system brought on by an imbalance in the gut microbiota. The two IBDs that are most well-known are ulcerative colitis (UC) and Crohn’s disease (CD). The purpose of the current study was to evaluate the Impact of smoking in inflammatory bowel disease.MethodsData of 373 patients with IBD divided into 209 Crohn’s disease and 164 with ulcerative colitis disease. cases were collected from king Abdulaziz medical city, Jeddah, Saudi Arabia from 2016-2022. Patients older than 18 years, Patients with a history of cancer other than colon cancer or other GIT disorders were excluded from consideration.ResultThis study involved 373 participants, predominantly with Crohn’s disease 209. The participants exhibited diverse smoking habits, with complications observed in 53.6% of cases. Smoking status and duration showed significant associations with complications, particularly in Crohn’s disease. For ulcerative colitis, smoking correlated with lower complication rates. The analysis of smoking variables and disease remission highlighted nuanced relationships, emphasizing the need for further exploration. Specific associations between smoking and Crohn’s disease site or ulcerative colitis subtypes were observed, suggesting potential influences on disease manifestations.ConclusionAccording to our research, smoking is negatively correlated with experiencing problems from ulcerative colitis (UC), and patients who smoke also appear to have higher rates of remission. Smoking has more issues with Crohn’s disease, though.